The plasma focus as a tool for plasma-wall-interaction studies. (March 2015) - Ramos, G; Martinez, M; Herrera, J J E; Castillo, F
Abstract: The study of the interaction of magnetized plasmas with candidate materials for fusion reactors, as for example tungsten, is a main topic in fusion research. Many studies simulate the plasma wall interaction using ion beams, while only a few use plasma simulators. Plasma foci can produce dense magnetized plasmas of deuterium and helium among other species. We used the plasma focus Fuego-Nuevo II, to expose tungsten samples to deuterium and helium plasmas. The samples were analysed by means of SEM, RBS and NRA, evidencing surface erosion, surface melting and retention of deuterium in a shallow surface layer of 250 nm amounting 6.5·10 16 D/cm 2 . The plasma temperature has been measured at the position of the samples using a triple Langmuir probe and compared to calculations of a snowplow model. The modelling of the electrode to reach desired plasma parameters is discussed.